The Impact of Glu102Lys on the Factor X Function in a Patient with a Doubly Homozygous Factor X Deficiency (Gla14Lys and Glu102Lys) - Forberg, Eva; Huhmann, Iris; Jimenez-Boj, Ester; Watzke, Herbert H. (Thrombosis and Haemostasis, 2000)
Two homozygous point mutations were found in a patient with factor X (FX) deficiency; One results in substitution of Lys for Gla+14 and the second causes a Lys substitution for Glu102. The proposita has a severely reduced FX coagulant activity in the extrinsic (<1% of normal) and in the intrinsic (30% of normal) system of coagulation and after activation with Russel’s viper venom (18% of normal). The FX antigen is reduced in this patient to 20% of normal. The substitution of Lys for Glu102 in FX deficiency has been reported previously in a heterozygous state in conjunction with a Lys for Gla+14 substitution and with a Pro for Ser334 substitution. The contribution of the Lys for Glu102 substitution in the observed combined FX defect in these patients was unclear. The mutation causing the Glu102Lys substitution was introduced by site directed mutagenesis into a wild-type FX cDNA, and recombinant protein was expressed in HEK 293 cells. Compared to the wild-type FX cDNA, the mutant construct had a 67% activity upon activation in the extrinsic system, 93% activity upon activation in the intrinsic system and 72% after activation with RVV. The data presented show that the substitution of Lys for Glu102 results in a minor functional defect of the FX molecule.
Keywords: Factor X; hereditary deficiency; factor X expression; second EGF domain